2015
DOI: 10.1016/j.jsat.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report After Randomly Assigned Supervision Does not Predict Ability to Practice Motivational Interviewing

Abstract: The objective of this study was to investigate the relation between self-report and objective assessment of Motivational Interviewing (MI) skills following training and supervision. After an MI workshop, 96 clinicians from 26 community programs (age 21–68, 65% female, 40.8% Black, 29.6% Caucasian, 24.5% Hispanic, 2.0% Asian, 3.1% other) were randomized to supervision (tele-conferencing or tape-based), or workshop only. At four time points, trainees completed a self-report of MI skill, using items from the MI U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…29 In that study, the latter group had greater and increasing results over time, reinforcing the importance of contemplating mechanisms for review, follow-up, and reinforcement of the main training. A community trial compared physicians who received only one training with another group that received additional teleconference supervision or recordings.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…29 In that study, the latter group had greater and increasing results over time, reinforcing the importance of contemplating mechanisms for review, follow-up, and reinforcement of the main training. A community trial compared physicians who received only one training with another group that received additional teleconference supervision or recordings.…”
Section: Discussionmentioning
confidence: 72%
“…A community trial compared physicians who received only one training with another group that received additional teleconference supervision or recordings. 29 In that study, the latter group had greater and increasing results over time, reinforcing the importance of contemplating mechanisms for review, follow-up, and reinforcement of the main training.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…First, this initial dissemination effort included no objective assessments of skill acquisition. Research has consistently demonstrated a tendency for trainees to overestimate their skills (Kruger & Dunning, 1999), an effect that has been repeatedly demonstrated in both medicine (Davis et al, 2006; Violato & Lockyer, 2006) and psychotherapy (Mathieson, Barnfield, & Beaumont, 2009; Wain et al, 2015). The relationship between the perceived and actual benefits of training is unknown in the present sample of workshop attendees.…”
Section: Discussionmentioning
confidence: 94%
“…Many substance-use treatment providers indicate that they are using MI principles in practice (Gifford et al, 2012), and it seems unlikely that practice-as-usual settings provide the MI intervention in its entirety and with high fidelity (Santa Ana et al, 2008). For example, professionals in the field overestimate their MI skills when their self-reported MI skills are compared to neutral expert ratings of their skills (Wain et al, 2015). Similarly, some research studies nominally of MI have included interventions not recognizable as MI (Miller & Rollnick, 2013), potentially skewing findings from metaanalyses on the effectiveness of MI studies.…”
Section: Why Focus On Best Practices In Teaching Mi?mentioning
confidence: 99%